Improved Beat Asynchrony Detection in Early Blind Individuals. (October 2014) - Lerens, Elodie; Araneda, Rodrigo; Renier, Laurent; De Volder, Anne G
Although early blind (EB) individuals are thought to have a better musical sense than sighted subjects, no study has investigated the musical rhythm and beat processing abilities in EB individuals. Using an adaptive 'up and down' procedure, we measured the beat asynchrony detection threshold and the duration discrimination threshold, in the auditory and vibrotactile modalities in both EB and sighted control (SC) subjects matched for age, gender, and musical experience. We observed that EB subjects were better than SC in the beat asynchrony detection task; that is, they showed lower thresholds than SC, both in the auditory and in the vibrotactile modalities. In addition, EB subjects had a lower threshold than SC for duration discrimination in the vibrotactile modality only. These improved beat asynchrony detection abilities may contribute to the known excellent musical abilities often observed in many blind subjects.